Determination of hydrodynamic properties of bovine serum albumin (BSA) - Curvale, Rolando (2010)
This work allows combining theoretical fundamentals along with the development of abilities and skills on applied hydrodynamics. This is a complementary tool used to establish or to confirm the structures and interactions of biomolecules, especially in diluted solutions. In this laboratory, viscosity measurements of bovine serum albumin solutions at different pH values are used to obtain parameters related to form and size of BSA conformers. This practice, which can be performed in three hours, presents the advantage of using low cost reagents and equipment common to many laboratories, which in turn facilitates student participation in their process of learning.